Pemberdayaan Ekonomi Masyarakat Melalui Budidaya Jamur Tiram Pada UMKM di Desa Batuampar Cermee Bondowoso - Budi Sufyanto; Imam Fahrurrozi; Zainol Hasan; Ahmad Khoironi (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
This activity aims to provide understanding to the community in Batuampar Village about the importance of community economic empowerment in local MSMEs. The focus of the community service is oyster mushroom cultivation. This focus was chosen because the level of demand for oyster mushrooms has increased and the increasing prevalence of sengon powder waste which can be used as a raw material in oyster mushroom cultivation. The method used is the Community Based Research method. The results of this service demonstrate the community's interest in generating independent income through oyster mushroom cultivation. This is demonstrated by the community's enthusiasm in participating in the extension and socialization activities from beginning to end.